2017
DOI: 10.17221/108/2017-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon localisation of a vegetal foreign body in a dog: a case report

Abstract: ABSTRACT:The goal of this study was to describe the ultrasonographic and computed tomographic appearance of a penile foreign body in a dog for the first time. We describe an unusual penile localisation of a grass seed awn in an 11-year-old mixed-breed dog referred for a computed tomography study after a severe haemorrhage from the penis. A fistulous tract was observed after plain and post-contrast whole-body computed tomography acquisition; the foreign body was localised with ultrasound and removed under ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…13,14 Grass seeds foreign bodies have been reported as causing disease in a number of diverse anatomical locations including the thorax, nasal cavity, ear, head, neck, penis, vagina, spine, shoulder and epidural space. 1,4,9,15,16 To the authors' knowledge, this is the first report of a grass seed migrating to the stifle.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…13,14 Grass seeds foreign bodies have been reported as causing disease in a number of diverse anatomical locations including the thorax, nasal cavity, ear, head, neck, penis, vagina, spine, shoulder and epidural space. 1,4,9,15,16 To the authors' knowledge, this is the first report of a grass seed migrating to the stifle.…”
Section: Discussionmentioning
confidence: 85%
“…17 In a published case of a penile grass seed, a similar tract, hypoattenuating and with irregular walls, was found in the left cavernous body of the penis, at the level of the caudal border of the os penis. 15 The tract in that case was also first been identified using CT. A study of CT findings in grass seed foreign body cases concluded that CT was most useful for localising secondary lesions rather than definitively diagnosing a grass seed. 4 These conclusions are consistent with this case, where the tubular tract from the grass seed migration was identified on CT, but the seed itself was not.…”
Section: Discussionmentioning
confidence: 98%
“…An uncommon cause of hemorrhagic preputial discharge is represented by the penetration of a foreign body into the foreskin or the connective tissue surrounding the penis [5,6], a condition which, according to the above mentioned hospital data of the last ten years, was approximately 2% of all cases of the hematuria or hemorrhagic preputial discharge in males.…”
Section: Discussionmentioning
confidence: 99%
“…A more complex diagnosis is represented by hematuria due to a foreign body embedded in the subcutaneous penile tissue [5]. It often represents a diagnostic challenge due to both the rarity of the event and to the frequent tendency, in the veterinary fi eld, not to carry out a sonographic exam of the penis during a routine urologic ultrasound procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation